2010
DOI: 10.1007/s11669-010-9672-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria and Crystal Chemistry in the System CaO-Al2O3-Y2O3

Abstract: The phase relations in the system CaO-Al 2 O 3 -Y 2 O 3 at 1400 and 1500°C have been determined. The phase relations presented are in agreement with the calculated phase diagram by Udalov et al. (Russ. J. Inorg. Chem., 1979, 24(10), p 1549-1553). In addition ternary solid solution series of the binary compounds YAM (Y 4 Al 2 O 9 ), YAP (YAlO 3 ), and YAG (Y 3 Al 5 O 12 ) could be described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The XRD patterns also proved that Y 2 O 3 did not react with CaO to form mixed oxides. This is consistent with the previous findings by Richter and Göbbels that the presence of binary Ca–Y oxides was not found in the sample even after being calcined at 1500 °C . It is worth mentioning that according to the calculation results of phase equilibrium by Udalov et al, only individual components exist as the phases in the binary CaO– Y 2 O 3 system at temperatures below 2000 K.…”
Section: Results and Discussionsupporting
confidence: 92%
“…The XRD patterns also proved that Y 2 O 3 did not react with CaO to form mixed oxides. This is consistent with the previous findings by Richter and Göbbels that the presence of binary Ca–Y oxides was not found in the sample even after being calcined at 1500 °C . It is worth mentioning that according to the calculation results of phase equilibrium by Udalov et al, only individual components exist as the phases in the binary CaO– Y 2 O 3 system at temperatures below 2000 K.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Compositions (% wt.) and melting points of eutectic batches (°С) [17]. X-Ray diffraction patterns were obtained with a DRON-3M (Bourevestnik, Russia) iffractometer operating at 40 kV and 10 mA and equipped with Cu Kα radiation (rotational rate 2 /min).…”
Section: Oxide Tectic Systemmentioning
confidence: 99%
“…Compositions (% wt.) and melting points of eutectic batches (°С)[17]. Structural formulae and characteristics of polymers.…”
mentioning
confidence: 99%
“…In the Y 2 O 3 ‐Al 2 O 3 ‐MgO system, only solid solutions at the sintering conditions can be formed 28,32 . Unlike MgO, CaO in the Y 2 O 3 ‐Al 2 O 3 ‐CaO system can form a small amount of liquid phase 33 . Zhou observed that using only MgO results in a lower temperature being needed for densification in comparison to CaO.…”
Section: Introductionmentioning
confidence: 99%
“…28,32 Unlike MgO, CaO in the Y 2 O 3 -Al 2 O 3 -CaO system can form a small amount of liquid phase. 33 Zhou observed that using only MgO results in a lower temperature being needed for densification in comparison to CaO. Both additives suppress grain growth; however, calcium oxide is more effective.…”
Section: Introductionmentioning
confidence: 99%